Constraints in Adoption of Climate Resilient Technologies in Rainfed Agro-Ecosystem - Jasna V. K. , R. Roy Burman , R. N. Padaria , J. P. Sharma , Eldho Varghese , Bidisha Chakrabarty, N. Loganandhan; Sanjay Kumar (Indian Journal of Extension Education, 2016)
Climate change and food security are the two daunting present day agrarian challenges. Adaptation through climate resilience is an undebatably accepted solution to better respond to these challenges. National Innovations in Climate Resilient Agriculture (NICRA) is an Indian Council of Agricultural Research (ICAR) initiative launched with a focus on making most vulnerable districts of the nation climate resilient. Since the inception of the project, a number of climate resilient technologies have been demonstrated across the country. The present investigation was undertaken with an objective to isolate the constraints in adoption of these technologies in rainfed agro-ecosystem. The results showed thatOfficials evaluated technical constraints, and labour and economic constraints as the most severe than that by the farmers.Among different technical factors, ’inadequacy of inputs’ stood first with mean rank 3.87 in hindering adoption as regarded by the farmers. But officials considered ’poor availability and accessibility of short duration drought tolerant crop varieties’ as the most severe one (mean rank is 3.3). Among labour and economic constraints, ’longer gestation period (mean ran k=3.74) to get the returns from adopted intervention’ and ’shortage of owned resources’(mean rank =3.95) were major constraints as per the opinion of farmers and officials, respectively. ’Resistance to change the conventional practices’ was considered as the most severe by both farmers(mean rank =3.99) and officials (mean rank = 4.05) in social and personal constraints. The findings will help in redesigning the already implemented interventions to ensure a higher adoption by managing the constraints.